Marginal neighborhoods in bogota’s urban ordering (2004)
The Zone Planning Unit (UPZ) are management and planning instruments, defined by the Territory Regulation Plan (POT), to regulate the urban use and treatment of localities organized at the interior of Minor city councils. This text contents an urban analysis and a planning project for the UPZ of Integral Improvement Treatment.